A tool for capacity building: teacher professional learning about teaching writing. Issue 5 (20th October 2018) - Johnston, Jenny; George, Stephanie
ABSTRACT: This paper reports on qualitative research from an Australian, K-6, faith-based school about teachers' experience of a job-embedded professional learning initiative (the Whole-School Benchmarking of Writing, WSBoW) that was designed to improve teachers' capacity to apply data-driven decision-making to achieve improvements in student learning. Teacher interviews provided the data about experiences and influences on teching practice. The findings demonstrated that the professional learning initiative provided teachers with a supportive pedagogical tool for focusing their teaching practices on improving student learning. A research based evaluative framework was used as a heuristic to analyse the change initiative. This study used the framework and employed a social constructivist and sociocultural epistemology that recognised the importance of leadership and school context in the development of a culture focused on collaborative communities of practice and data-driven teacher decision-making. The study has significance for leaders, schools and systems that engage teachers in professional capacity building.